Your success, our passion - Eswaran, Vijay, Dato'; Balagtas,Chandravali Dasi; Munian, Maralikrishnan; VStudios ([S.l.] : VStudios, 2008)
A talk by Dato' Vijay Eswaran about the success in social networking or multilevel marketing
Title from title screen
Executive producer, Pathman Senathirajah
DVD format
Keywords: Multilevel marketing; Direct marketing